2006
DOI: 10.1037/0012-1649.42.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Friend influence on prosocial behavior: The role of motivational factors and friendship characteristics.

Abstract: This study examined motivation (prosocial goals), individual characteristics (sex, ethnicity, and grade), and friendship characteristics (affective quality, interaction frequency, and friendship stability) in relation to middle adolescents' prosocial behavior over time. Ninth- and 10th-grade students (N = 208) attending a suburban, mid-Atlantic public high school and having at least 1 reciprocated friendship were followed for 1 year. Hierarchical regression analyses revealed that a friend's behavior is related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 62 publications
6
147
0
7
Order By: Relevance
“…For boys no such relationship was found. Similarly, peer support (Wentzel, 1994), peer expectations (Wentzel, Filisetti & Looney, 2007) and peer prosocial behavior (Barry & Wentzel, 2006) have been related to prosocial goal endorsement at school.…”
Section: Processesmentioning
confidence: 97%
“…For boys no such relationship was found. Similarly, peer support (Wentzel, 1994), peer expectations (Wentzel, Filisetti & Looney, 2007) and peer prosocial behavior (Barry & Wentzel, 2006) have been related to prosocial goal endorsement at school.…”
Section: Processesmentioning
confidence: 97%
“…Prior research suggests that 'peer' is an important environmental source for the development of PB (Barry & Wentzel, 2006). In less cohesive environments, non-shared environmental factors such as parental differential treatment or conflicts with family members may influence adolescents' prosocial development by moderating peer relations and/or characteristics of friends they associate with.…”
Section: Figurementioning
confidence: 99%
“…Integration of positive peer relationships within intervention efforts has been shown to divert youth from problem behaviors, where for example studies have found that peers' prosocial behavior decreases delinquent attitudes (Carson, 2013) as well as promotes prosocial behavior (Barry & Wentzel, 2006). Since all of the participants described having access to peers who do not engage in delinquency and recon that these relationships were a source of support in avoiding future delinquency, practitioners could encourage them to move closer to these friends, as this is more realistic and palatable, than to develop entirely new network of same aged companions.…”
Section: Implications and Future Directionsmentioning
confidence: 99%